Transient Analysis of Single Server Queueing system with Loss and Feedback - Sivanandam, S. Shanthi; Subramanian, A. Muthu Ganapathi; Sekar, Gopal (International Journal of Computer Sciences and Engineering, 2025)
Consider a single server queueing system with Loss and Feedback in which customers arrive in a Poisson process with arrival rate λ and service time follows an exponential distribution with parameter μ. If the server is free at the time of an arrival of a customer, the arriving customer begins to be served immediately by the server and satisfied customer leaves the system with probability (1-q) after the service completion and dissatisfied customers will join the queue with probability q to get service once again. This is called Feedback in queueing terminology. If the server is busy, then the arriving customer will join the queue with probability p in front of service station. This is called Loss in queueing terminology. In this paper, we have derived the closed form solutions of time dependent probabilities of the single server queueing systems with Loss and Feedback. The corresponding Transient distributions have been obtained. We also obtain the time dependent performance measures of the systems.